Evaluasi Kinerja Unit Crushing Plant dalam Upaya untuk Meningkatkan Target Produksi Batu Split di PT Semen Padang - Mutia Sri Rezeki; Murad Murad (Journals Mining Engineering : Bina Tambang, 2018)
PT Semen Padang is a manufacturer of cement in Indonesia and also split stone production. Split stone is processed by using the crushing plant. Based on data of split stone production at PT Semen Padang in March 2018, the company’s split stone target production of 18.900 tons/month was not reached. At the same time, the actual production obtained was 3.799,23 tons/month. This is caused by many disturbances of repair time during split stone processing and wore out the jaw crusher, so that the effective working time being reduced. Related to this problem it is necessary repair to increase split stone production target. Repair made is reduction of repair time such as replacement motor pulley and reversal of liner jaw crusher because wearing out. The result obtained pf this research after the repair occured reduction of repair time, so that effective working time became increased, the value of avaibility became increased, and effectiveness of jaw crusher also increased. The production of split stone obtained in April was 43,03% in which split stone production in March was 3.799,23 tons/month increased to 5.472,23 tons/month in April. Keywords:  Production, Crushing Plant, Split Stone, Disturbance, Repair Time